Strategi Misi Rasul Paulus Dalam Pekabaran Injil - Maria Widiastuti (Jurnal Christian Humaniora, 2021)
Abstract:The mission of evangelism is to share or give the good news to others. The good news is that Jesus Christ was given by the church that He died and rose from the dead for the redemption of sinners. Strategy means, the plan in its entirety, the principles or ways in which the means will be used in the task. While the mission according to strategy is, “the way the body of Christ strives to obey God and fulfill the goals He has set.” So, the mission strategy is a plan that enables the ministry of the church to achieve its goal of making all ethnic groups become disciples of Christ (Matt. 28:18-20). The Strategy of Paul's approach to the mission of evangelizing in this discussion is: First: Paul serves contextually and is sensitive to the local culture that is his target. He adapted himself to the local culture and used their language in his mission. Second: geographically Paul looks for big cities as priority targets in his missions. Third: Paul builds a work team in evangelism and discipleship then sends out to areas. Keywords: mission, strategy, paul  Abstrak:Misi pekabaran Injil adalah membagi atau memberitakan kabar baik kepada orang lain. Kabar Baik tersebut ialah Yesus Kristus yang diberitakan oleh gereja bahwa Ia telah mati dan bangkit dari antara orang mati bagi penebusan manusia berdosa. Strategi berarti, rencana dalam keseluruhannya, prinsip-prinsip atau cara-cara di mana sarana-sarana yang akan dipergunakan dalam tugas. Sedangkan strategi misi menurut kekristenan adalah, “cara Tubuh Kristus mengupayakan dalam mentaati Tuhan dan menggenapi tujuan-tujuan yang telah ditetapkan-Nya.” Jadi, strategi misi sebagai rencana yang memungkinkan pelayanan gereja meraih sasarannya yaitu menjadikan segala suku bangsa menjadi murid Kristus (Mat. 28:18-20). Strategi pendekatan Paulus dalam misi pekabaran Injil di dalam pembahasan ini adalah Pertama: Paulus melayani secara kontekstual dan sensitif terhadap budaya lokal yng menjadi sasrannya. Paulus juga menyesuaikan diri terhadap budaya lokal dan menggunakan bahasa mereka dalam pelayanan misinya. Kedua: secara geografis Paulus mencari kota-kota yang besar sebagai sasaran prioritas dalam misi-misinya. Ketiga: Paulus membangun tim kerja dalam penginjilan dan memuridkan kemudian mengutus ke daerah-daerah. Kata kunci: misi, strategi, paulus